Residual nitrogen fertilization effect of common bean production on succeeding corn intercropped with Congo grass - Carmeis Filho, Antonio Carlos Almeida; Cunha, Tatiana Pagan Loeiro da; Mingotte, Fábio Luiz Checchio; Martins, Isaac Silva; Lemos, Leandro Borges; Fornasieri Filho, Domingos (Revista Ceres, 2016)
Crop production in conservation systems involving intercropped cultivations mainly with corn have been proposed as a technology to promote sustainability in the Brazilian Cerrado areas. The objective of this work was to evaluate the influence of residual nitrogen fertilization applied in common bean on subsequent corn sole or intercropped with Congo grass (Urochloa ruziziensis) in no-tillage system. The experiment was carried out in randomized blocks with three replicates in a split-plot design. The treatments were composed by two cropping systems (sole and intercropped with Congo grass), and the sub-plots were five doses of nitrogen (0; 40; 80; 120 and 160 kg of N ha-1), applied in topdressing on common-bean (previous crop). There was no effect of cropping systems and residual amount of nitrogen application in the vegetative and reproductive development of corn. Corn intercropped with Congo grass leaded an adequate formation of crop residue and total land covering target at sustainability of no-tillage system.